The Relationship Between Mothers’ Knowledge of the Benefits of Infant Massage and the Frequency of Infant Massage Practice - Yaumil Fauziah; Rahmi Mutia Ulfa; Fitri Khairani (JWHM : Journal of Women's Health and Midwifepreneurship, 2026)
Introduction: Infant massage provides various benefits for infants, including supporting growth, improving sleep quality, and strengthening mother–infant bonding. Mothers’ knowledge may influence how regularly infant massage is practiced. Novelty: This study examines the relationship between mothers’ knowledge of infant massage benefits and the frequency of practice in Medan Sunggal. Its novelty lies in emphasizing the consistency of infant massage practice within a community setting, an aspect rarely addressed in studies. Methods: This study used a correlational design with a cross-sectional approach. The population consisted of all mothers with infants in Medan Sunggal, totaling 94 people. The sampling technique used was purposive sampling, with 48 respondents who met the inclusion and exclusion criteria. Data were collected using questionnaires and analyzed using the chi-square test. Results: The results showed that mothers with good knowledge who regularly performed infant massage were 4.2%, while those who did not perform it regularly were 4.2%. Mothers with sufficient knowledge who regularly performed infant massage were 22.9%, while those who did not perform it regularly were 27.1%. Meanwhile, mothers with poor knowledge who regularly performed infant massage were 4.2%, while those who did not perform it regularly were 37.5%. The statistical test showed an Asymp. Sig. (2-sided) value of 0.027 < 0.05, indicating a significant relationship between mothers’ knowledge of the benefits of infant massage and the frequency of infant massage practice. Conclusion and Suggestions: Mothers should improve their knowledge of infant massage, while health workers should provide regular education to support correct and consistent practice.